Implementation of Changes in an Organization by the Management and Its Impact on Employees Attitude - JAHANGIR, Muhammad; ZIA-UR-REHMAN, Muhammad; IRFAD, Muhammad (Asian Journal of Empirical Research, 2013)
In the post-modern world of today, the economy of the world is developing at an astounding pace and the world has become a global village. Organizations are trying to capture the markets by attracting more customers through diverse and novel activities to compete with their counterparts. The rationale of the study is based on the role of management in the implementation of change initiatives and their impact on employee’s attitude. The Sainsbury Store located in London Conley has been considered as a case study. The data were gathered on the basis of observations and also through a detailed questionnaire based on close-ended and open-ended questions, which were distributed among the managers and the employees. The study was carried out by randomly picking 5-10 managers and 25-30 employees as a sample size. Collected data were analyzed and the deduced findings demonstrate that there were just few employees had bad experiences, not about the change but about the management of the store. At the end, to overcome this and various other issues and to improve the change process, certain recommendations were presented to the management of the store.